Решить уравнения. 4х - 8 * (3х - 2) + 4 * (5- 2х) - 6 (3-х) 2*(4-3х) - (х+ 7) + 9* (х-5) - 6* (х+1)

ксюшка485456 ксюшка485456    2   22.05.2019 14:20    1

Ответы
staisywell1 staisywell1  18.06.2020 01:08
4х-8*(3х-2)+4*(5-2х)-6*(3-х)=4х-24х+16+20-8х-18+6х=
=18х+18=18(х+1)
2) 2*(4-3х)-(х+7)+9*(х-5)-6*(х+1)=8-6х-х-7+9х-45-6х-6=
=-4х-50=-2(2х+25)
ПОКАЗАТЬ ОТВЕТЫ
tyoma2223333 tyoma2223333  18.06.2020 01:08
1)4х - 8 * (3х - 2) + 4 * (5- 2х) - 6 (3-х)=4x-24x+16+20-8x-18+6x=18+18x
2)2*(4-3х) - (х+ 7) + 9* (х-5) - 6* (х+1)=8-6x-x-7+9x-45-6x-6=-50-4x
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика